2002
DOI: 10.1103/physrevlett.89.088302
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Drag Reduction and Degradation of DNA

Abstract: Turbulent drag reduction induced by lambda-DNA is studied. The double-stranded DNA is found to be a good drag reducer when compared with the other normal linear polymers. However, this drag reducing power disappears when the DNA denatures to form two single-strand molecules. Mechanical degradation of DNA is also different from that of the normal linear-chain polymers: DNA is always cut in half by the turbulence. Our results suggest that the mechanism for turbulent degradation of DNA is different from that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 19 publications
8
74
0
Order By: Relevance
“…13. The middle curve corresponds to Re= 1.2 × 10 6 , which coincides with the experimental conditions (Choi et al, 2002). One sees, however, that the dependence of %DR on Re is rather weak.…”
Section: B Drag Reduction When Polymers Are Degradedsupporting
confidence: 82%
See 2 more Smart Citations
“…13. The middle curve corresponds to Re= 1.2 × 10 6 , which coincides with the experimental conditions (Choi et al, 2002). One sees, however, that the dependence of %DR on Re is rather weak.…”
Section: B Drag Reduction When Polymers Are Degradedsupporting
confidence: 82%
“…13 is that for small Q (actually for Q ≤ 0.5 or %DR ≤ 20), %DR is approximately a linear function of Q. The experiments (Choi et al, 2002) …”
Section: B Drag Reduction When Polymers Are Degradedmentioning
confidence: 85%
See 1 more Smart Citation
“…The DNA molecules can change from their double-stranded state to two single-strands under certain temperature or pH conditions. Based on the above property, Choi et al [98] employed λ-DNA as a drag reducing agent to probe the mechanism of drag reduction and mechanical molecular degradation. They reported that λ-DNA is considered to be a better polymeric DR additive than the high-molecular-weight linear long-chain PEO.…”
Section: Dnamentioning
confidence: 99%
“…J. Choi et al (2002) studied the turbulent drag reduction induced by λ-DNA and compared it with a high molecular weight polyethylene oxide (PEO) (Mw=5 *10 6 ) using rotating disk apparatus (RDA). Moreover, the transient behaviour of the mechanical molecular degradation (MMD) of DNA chains in a turbulent flow was investigated.…”
Section: Drag Reduction Using Rotating Disk Apparatus (Rda)mentioning
confidence: 99%